2022
DOI: 10.1002/fsn3.2869
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary probiotics supplementation on meat quality, volatile flavor compounds, muscle fiber characteristics, and antioxidant capacity in lambs

Abstract: This study investigated the effects of probiotics on growth performance, meat quality, muscle fiber characteristics, volatile compounds, and antioxidant capacity in lambs. A total of 24 Sunit lambs were randomly allocated into two groups, each consisting of three replicates of four lambs. Throughout the experiment period, the lambs were fed with based diet (CON) and 10 g probiotics/d supplemented diet (PRO). Compared with the CON group, the number of lactic acid bacteria in fecal samples of PRO group was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 80 publications
3
20
0
Order By: Relevance
“… 2 The odor descriptions of volatile compounds referred to ( He et al, 2022 ; Liu et al, 2022 ; Liu et al, 2023 ); CON, DL1, and DL2 represent groups feed diets containing 0%, 1%, and 5% DOL, respectively. …”
Section: Resultsmentioning
confidence: 99%
“… 2 The odor descriptions of volatile compounds referred to ( He et al, 2022 ; Liu et al, 2022 ; Liu et al, 2023 ); CON, DL1, and DL2 represent groups feed diets containing 0%, 1%, and 5% DOL, respectively. …”
Section: Resultsmentioning
confidence: 99%
“…Positive attributes, such as umami and juicy flavors in grain-fed steaks, are correlated with 1-octen-3-ol ( Song et al, 2011 ). 1-Pentanol has a strong, sweet, balsamic aroma ( Liu et al, 2022 ). Meanwhile, the dominant bacterial community was Carnobacterium , including that could produce these VOCs at low temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Long‐term feeding with probiotic Lactobacillus reuteri 1 improved pork quality by increasing the water‐holding capacity and tenderness and altered the muscle fibre characteristics; for example, the myofibre diameter and cross‐sectional area were decreased (Tian et al., 2021 ). In sheep, the addition of a mixture of Lactobacillus casei HM‐09 and Lactobacillus plantarum HM‐10 to the diet improved tenderness by decreasing the average muscle fibre cross‐sectional area and switching from type IIB fibres to type I fibres (Liu et al., 2022 ). Likewise, another study reported that dietary supplementation with Lactobacillus groups ( L. casei HM‐09 and L. plantarum HM‐10) could regulate the AMPK signalling pathway to foster the conversion of myofibres from the glycolytic to the oxidative type, which improves meat quality (Wang, Yan, et al., 2022 ).…”
Section: Faecal Microbiota Transplantation and Probiotic Supplementat...mentioning
confidence: 99%